Development Through the Lenses of Migration - Siddiqui, Shah Alam (South Asian Journal of Social Sciences and Humanities, 2022)
This article examines the impact of migration on society, both how it is measured and analysed. Migration was the most critical force driving India’s otherwise idyllic progress in the twentieth century. Researchers found that skilled emigration is rising in developing countries and that rich countries are increasingly turning to foreign workers with advanced training to fuel domestic innovation. This study discusses migration and skill development and social, economic, and technological innovation in depth. In this case, the research is descriptive. The information was gathered through secondary sources such as journals and books.